Impact of Japanese Popular Culture as Learning Resources on Students' Japanese Learning Achievement - Muhammad Thamrin; Robihim Robihim (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to determine the influence of Japanese popular culture as a learning resource on students' Japanese language learning achievement. A quasi-experiment with a pretest and posttest one-group experimental design was used as the research method. Two classes were used to conduct this research, namely the Japanese writing and speaking classes at Japanese Education, Darma Persada University, Jakarta. Each class consists of 30 students. Data is taken from test results, observations and documents. The data analysis technique uses a two-sample paired t-test for the mean. The results of the t-test data analysis show that Japanese popular culture can be used as an authentic learning source in the classroom, and student learning outcomes in Japanese writing and speaking classes have increased from the previous semester. The result of data analysis using a t-test can be seen from the Japanese writing class showing that t Stat t-table (-30.0667 2.0452) and the Japanese speaking class showing that t Stat t-table (-20.5542 2.0452). So, the results of this research have implications for understanding the use of learning resources that are familiar to students and appropriate to the context of students' lives